Accelerated maturation of processed yerba-mate under the controlled conditions of temperature and humidity. Issue 4 (13th July 2015) - Gonçalves, Itamar Luís; Dartora, Nessana; Piovezan Borges, Ana Cláudia; Picolo, Ana Paula; Dallago, Rogério Marcos; Mera de Souza, Lauro; Valduga, Alice Teresa
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper was to assess the changes in secondary metabolites and color during yerba-mate aging under controlled conditions. In Uruguay and Paraguay, the yerba-mate matured, in which chlorophyll degradation occurs, is preferred. For the matured product, the yerba-mate is stored for six months to one year. Design/methodology/approach – Processed yerba-mate was submitted to 35°C and 80 per cent humidity during 42 days in a climatic chamber. Samples were collected every seven days, and the phenolic compounds/methylxanthines were quantified by ultra-performance liquid chromatography – photodiode array and chlorophylls/phaeophytins by spectrophotometry. L*, a* and b* colorimetric coordinates were measured. Findings – The most expressive changes in the color occur in the first 14 days. At this time, 23.161 ± 2.984 per cent of total chlorophyll was degraded, considering that in 42 days, 37.458 ± 0.955 per cent is degraded, according to an exponential model. A positive correlation between theobromine amount and maturation time was found. This was verified by an increase in dicaffeoylquinic acid concentrations and small changes in chlorogenic acid isomers. Practical implications – The results indicate that this is a viable accelerated yerba-mate maturation process according to economics and nutraceutics. Originality/value – The paper has reported here a novel strategy to promote the yerba-mate maturation using controlled conditions.